Copper status tropical soils and critical levels for Brassica rapa L. var. Parachinensis - Hani, Nurul Wahida (2014)
Copper is one of the essential micronutrients required in small amounts however it will impair plant growth and cause toxicity when present in high concentrations. The use of agrochemicals in intensive agricultural land causes Cu build up in the soils.The availability of Cu to plants depends on its mobility which partly controlled by its association with soil constituents. The goals of this study were to assess the Cu concentration and phase associations in intensive vegetable farms; to evaluate Cu sorption-desorption in Oxisol, Inceptisol and Histosol; to evaluate Brassica rapa response to increasing soil Cu concentration and phase associations in the mineral soils. Soil sampling took place in selected conventional and organic farms in Cameron Highlands, Pahang while one organic farm was chosen in Bangi, Selangor. Copper phase associations were analyzed using Cu sequential extraction (Salas et al., 1998) while soil pH, CEC, total carbon and free Fe, Al and Mn oxides were determined too. Assessment of soils in vegetable farms showed that soil Cu content in conventional (33.61 mg Cu kg-1) and organic (11.91 mg Cu kg-1) vegetable farms in the highland contained higher Cu than the forest soil (2.72 mg Cu kg-1). There was no significant difference in Cu content between soil of organic farms of highland (11.91 mg kg-1) and lowland (12.79 mg kg-1). This study found that the increase in Cu content was associated with higher pH, CEC and total carbon. Organic matter was found to be the main component that controls the fate of Cu in the cultivated soil under study. Longer operation farm period, routine application of fungicides and chicken manure leads to higher Cu concentration in conventional farm.The Cu sorption isotherm was carried out in a batch experiment where 1:10 ratio of soil to solution equilibrated with 0.01M CaCl2 solution containing 5, 10, 15, 20, 30,60 and 100 mg L-1 Cu as CuCl2, followed by desorption of Cu. Uncultivated soils from Oxisol (Munchong Series), Inceptisol (Selangor Series) and Histosol (peat) were used in this study. Results showed that Histosol had the highest sorption capacity followed by Oxisol and Inceptisol. The Freundlich model was found to be better in describing the sorption isotherms of Oxisol (74.82 L kg-1, R2=0.99) and Histosol (688.65 L kg-1, R2=0.99). Copper sorption in Inceptisol was well described (R2=0.98) by the Langmuir model which provides the maximum adsorption value of 384.62 mg kg-1. Histosol had the least tendency to desorb Cu followed by Oxisol and Inceptisol at 100 μg mL-1 Cu loading. The sorption-desorption capacity is influenced by the CEC, organic matter content, Fe and Al oxides and clays. A factorial pot experiment was carried out to determine the Cu critical and toxicity threshold levels for Brassica rapa in Oxisol, Inceptisol and Histosol. Copper sulphate solution was applied at the rates of 0, 5, 10, 15, 20, 30 and 60 mg Cu kg-1 soil. The yield response of plant on Oxisol, Inceptisol and Histosol are expressed in quadratic equations of y-1 = 1.422–0.244x+0.014x2, y-1 = 0.626–0.084x+ 0.005x2 and y =1.678+0.198x–0.007x2, respectively. The soil Cu critical level in Oxisol, Inceptisol and Histosol is 7.34, 5.96 and 7.40 mg kg-1, respectively; and threshold toxicity level is 10.63, 10.92 and 21.64 mg kg-1, respectively. Both Cu levels are in consistence with the soils desorption capacity and the concentration of Cu mobile fraction as defined as summation of water soluble and exchangeable fractions. Height of plants and the SPAD value of leaves decreased with increasing Cu concentration. Copper phase associations in Oxisol and Inceptisol were determined using sequential extraction method. Both soils were found to have the same order of Cu fractions of organic > residual > Fe/Mn oxides > carbonates > exchangeable > water soluble.